Wpływ języka angielskiego na słownictwo i pisownię rozmów IRC w języku polskim i rosyjskim - wybrane zagadnienia - Kuczyński, Bartosz (Acta Polono-Ruthenica, 2006)
The following article examines a variety of elements concerning the influence of the English language on the vocabulary and spelling of the IRC chats in Polish and Russian. After a short presentation of the IRC service itself and the conversations made through it, a number of examples of the jargon, the youth slang, the play with spelling, and the transcription of the Cyrillic alphabet, which appear in the medium, are presented. Most of the examples serve to illustrate the influence of the English upon the Polish and the Russian languages of the IRC users. Additionally, the examples prove the author’s assumption that IRC is a medium which stimulates linguistic creativity